The rise, fall and potential for a rebirth of receivership in UK corporate law. Issue 1 (2nd January 2020) - Akintola, Kayode; Milman, David
ABSTRACT: In this article, we explore diverse forms of receivership in order to demonstrate the extent of the continued or potential utility of this institution in UK Corporate Law. We do this by placing the historical origins of receivership alongside its contemporary manifestations in both solvent and insolvent scenarios. In so doing, we present a nuanced picture of receivership as a process that, in specie and – by reference to outcomes in other corporate insolvency law procedures – in substance, continues to provide protection for creditors (and other stakeholders) in modern commercial transactions.